Food and Agriculture in Ethiopia: Progress and Policy Challenges - PAUL A. DOROSH, SHAHIDUR RASHID (University of Pennsylvania Press, International, 2013)
Food security issues in Ethiopia are extremely complex because of large variations across space and over time related to agroecologies, weather shocks, government policies, and other factors. In this context, Ethiopia’s agricultural and food policies are crucially important, having profound effects on tens of millions of low-income people throughout the country. Following major famines in the 1970s and 1980s, the country has made huge strides in the past two decades—increasing food production, promoting market development, building an effective safety net for millions of foodinsecure households, improving its disaster food emergency response capabilities, and laying a foundation for future economic growth. Yet there is much to be done to reduce the still-high levels of food insecurity. This book describes these past developments and the policies likely to shape future trends. The analysis it contains builds on and extends a long history of IFPRI work in Ethiopia in collaboration with the Ethiopian Development Research Institute and researchers at Addis Ababa University, including work on causes of and responses to major famines in Ethiopia in the 1970s and 1980s, rural poverty dynamics, analyses of cereal markets that helped lead to the creation of the Ethiopian Commodity Exchange, and the impact of the Productive Safety Net Programme. The analysis presented in this book shows the importance of continued investments in increasing agricultural productivity in order to promote both economic growth and poverty reduction. The book also highlights fi ve major challenges Ethiopia must face to achieve high economic growth rates, reduce poverty, and enhance household food security: sustaining growth in crop and livestock production, increasing market effi ciency, providing effective safety nets, maintaining macroeconomic incentives and stability, and managing the rural–urban transformation. If these challenges are met, there is good reason to expect that Ethiopia will enjoy further progress in reducing poverty and enhancing food security.